Control administrativo y su incidencia en la gestión financiera de la cooperativa de ahorro y crédito 29 de octubre, período 2010-2012, sistema de control de riesgos. - Bustamante Vera, Freddy Hernán (2013)
This research was conducted with the objective of evaluating the Administrative Control and its Impact on the Financial Management of the Cooperative Credit Union “29 of October” Ltd. Period 2010 to 2012, based on the problems found in How affects administrative control financial management of the Cooperative Credit Union Ltd. October 29? This research contributes an appropriate administrative system to the organizational structure of the Cooperative “29 of October” Ltd., besides knowing the liquidity and profitability of the branch has Quevedo and hypothesized that the poor negatively affects Administrative Control Financial Management Cooperative Credit Union “29 of October” Ltd. The research has a quantitative approach, and that the resulting data could be measured through descriptive statistics, so the information was collected through field research and literature - documentary. The techniques used in the development of this research was the survey and interview, which allowed them to be in direct contact with the problems of the Cooperative. In which took the customer information from the Cooperative Credit Union, staff and management of the Agency Quevedo also for obtaining financial indices did from information published by the Superintendency of Banks. As relevant result is observed that inadequate recovery of the portfolio, is caused by the poor administrative control that produces the same instability in financial management that is missing compliance fundamentals of the Cooperative, besides existing gaps in procedures administrative control, so that run certain activities to personal criteria and this causes instability in financial management. ........................................................................................